Critical Obstetric Patients During the Coronavirus Disease 2019 Pandemic: Operationalizing an Obstetric Intensive Care Unit. Issue 3 (25th September 2021) - Martinez, R.; Bernstein, K.; Ring, L.; Ona, S.; Baptiste, C.; Syeda, S.; Aziz, A.; Robinson, K.; Valderrama, N.; Sheen, J.-J.; D'Alton, M.; Goffman, D.; et al.
Abstract : ( Anesth Analg . 2021;132:46–51) In the early months of the coronavirus pandemic, the incidence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in pregnant patients presenting to labor and delivery (L&D) units in New York City was 15.4%. As intensive care unit (ICU) beds became scarce and nonemergent surgeries were halted, one large academic institution in NYC decided to create an obstetric intensive care unit (OBICU), which was fully operational by the end of March 2020. This article describes how the hospital staffed and operated the OBICU to treat critically ill peripartum patients with a quality of care equal to that of a surgical or medical ICU.